Changes in the phytoplankton structure downstream a large reservoir: effects of tributaries on the assemblages attributes - Matsuura, Patricia [UNESP]; Perbiche-Neves, Gilmar; Ferreira, Rosa Antonia Romero [UNESP]; Nogueira, Marcos Gomes [UNESP] (Walter De Gruyter Gmbh, 2015)
Changes in richness, diversity, evenness and abundance of phytoplankton in relation to environmental variables and tributary entrances were studied along 30 km of the Parana River downstream Itaipu Reservoir. A high number of taxa was found, 315. The Parana River differed from the tributaries Iguacu River and Monday River. The phytoplankton and limnological characteristics of the Parana River changed after the entrance of these tributaries. Higher values of richness and alpha diversity of phytoplankton were found in the two tributary rivers, which also produced an increase in the corresponding mean values in the Parana River. Higher values of total abundance and lower values of evenness were found at the dam site with typical lentic conditions. The assemblages of the two tributary rivers were homogeneous. Bellow dam the phytoplankton exhibited a decrease in abundance and an increase in evenness. Water transparency, water flow, nutrients and turbidity were the main indicators of the system spatial heterogeneity. Several species were correlated with silicate, redox potential and/or water temperature. Reservoir conditions promote conspicuous differences in the phytoplankton of the Parana River. The downstream reorganization of the community, with a sharp decrease in abundance, is positively influenced by tributary rivers in terms of richness and diversity.
Keywords: Abundance; Diversity; gradient; Itaipu reservoir; Parana River; Potamoplankton; Richness